Optimal investment and marketing strategies - Murynets, Ilona (Hackensack, NJ : World Scientific, 2012)
'Over the past decade, innovative technologies have resulted in an extensive growth of new services. Each new service requires a number of management and marketing decisions to be made well in advance of its launch and throughout its entire life cycle. This book develops mathematical models to facilitate decision-making dealing with technologically innovative services. Specifically, it develops (i) models for optimal pricing strategies of subscription services on monopolistic and duopolistic markets; (ii) an analytical model for optimal investment and optimal pricing strategies for innovative maintenance service contracts; and (iii) a model for targeting customers in marketing campaigns. In addition, the models (i)-(iii) can also be used to forecast an aggregate demand for a new service as well as the service demand for each individual customer.'--Publisher's website.
Introduction -- Literature review -- Migration of customers and targeting customers for marketing campaigns -- Optimal service pricing (single-period model) -- Optimal new service pricing in monopoly (dynamic model) -- Optimal new service pricing in duopoly (dynamic model) -- Optimal investment and pricing --Strategies for post-production service contracts.
Includes bibliographical references (p. 73-79).
Keywords: Investments -- Mathematical models; Pricing -- Mathematical models; Customer services -- Prices -- Mathematical models